The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1097/00000542-200208000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Low-volume Acute Normovolemic Hemodilution in Adult Open-heart Surgery

Abstract: In patients undergoing elective open-heart surgery, low-volume ANH showed lack of efficacy in reducing the need for allogeneic transfusions and postoperative bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
3
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 28 publications
2
29
3
3
Order By: Relevance
“…More recent studies have been published, with negative results. 65,66 However, in these studies, low-volume ANH was added to a well-defined blood conservation approach aiming at decreasing perioperative blood losses by the use of cell saving techniques and the administration of aprotinin or tranexamic acid. As a result, the hematocrit (or the hemoglobin concentration) before leaving the operating room was similar in the control and ANH patients.…”
Section: Results From the Literaturementioning
confidence: 99%
“…More recent studies have been published, with negative results. 65,66 However, in these studies, low-volume ANH was added to a well-defined blood conservation approach aiming at decreasing perioperative blood losses by the use of cell saving techniques and the administration of aprotinin or tranexamic acid. As a result, the hematocrit (or the hemoglobin concentration) before leaving the operating room was similar in the control and ANH patients.…”
Section: Results From the Literaturementioning
confidence: 99%
“…~3-~7 Hohn et at. conducted a prospective randomized study of 77 patients undergoing cardiac operations under moderate hypothermia, which showed 15 and they also found that low-volume ANH lacked efficacy. These were properly planned, randomized prospective trials, but the subjects underwent only relatively low invasive procedures, in terms of both surgical procedures performed and CPB conditions.…”
Section: Discussionmentioning
confidence: 99%
“…ANH is accomplished by drawing a unit of the patient's blood at the beginning of the surgery while administering 500 ml of colloid solution, and returning the autologous blood at the end of the surgery. This technique is used routinely in cardiac surgery and was tried in other major operations as part of blood conservation strategies with the purpose of reducing homologous blood transfusion [12][13][14]. We hypothesized that ANH could assist in lowering blood pressure during the surgery, thereby reducing the need for hypotensive drugs or other agents that decrease blood pressure.…”
Section: Introductionmentioning
confidence: 99%